INHALATION THERAPY IN CHILDREN: ISSUES AND OPTIONS - L. R. Selimzyanova; E. А. Promyslova; E. А. Vishnyeva (Вопросы современной педиатрии)
Today inhalation therapy forms the basis of treatment for children and adults with bronchial asthma. In the current market there is a great number of various drug delivery systems, such as: nebulisers, pressurised metered-dose inhalers and dry powder inhalers. Guidelines for diagnosis and management of bronchial asthma present preferred and alternative devices for treatment of children in their age group. Although choosing an inhaler device one should consider not only age and cognitive peculiarities in each patient, but also his individual preferences. Poor compliance with treatment in bronchial asthma is often due to the fact that a patient experiences problems using a dosage device. Though it is known that the effective inhalation therapy is achieved by following correct inhalation techniques given in guidelines to the concrete device. Incorrect inhaler use causes loss of asthma control. Meanwhile just one half of patients can use the medication correctly after self-studying of guidelines. Consequently, a physician should train a patient to use the device and control his actions. Up-to-date delivery systems for inhalation therapy and principles of their selection in children’s treatment are considered in the article. The survey of research data concerning the use of dry powder inhaler type-easyhaler is presented as well.